A model of student smoking cessation behavior based on pictorial health warnings as an intervening variable - Arif Julianto Sri Nugroho; Anis Marjukah; Dandang Setyawanti; Abdul Haris; Ummu Hany Almasitoh; Tasari Tasari (Goodwood Publishing, 2025)
Purpose: This research examines smoking cessation among students at seven universities following pictorial health warnings under Government Regulation No. 28 of 2024 on Tobacco Control. Using the Theory of Planned Behavior, it analyzes how attitudes toward smoking’s health impacts and perceived behavioral control influence smoking cessation through pictorial warnings as an intervening variable, aiming to foster a healthier Indonesian society. Research Methodology: This quantitative study used purposive sampling with 200 student respondents who quit smoking at seven universities in Soloraya. Data were collected through surveys and interviews, analyzed using item validity, reliability, goodness-of-fit, and Structural Equation Modeling (SEM) to test variable influences, with moderating analysis conducted via AMOS 21. Results: The results of quantitative research showed that two independent variables directly influenced students' smoking cessation behavior, with attitude having a dominant influence. Pictorial health warnings acted as an intervening variable. Conclusions: The research concludes that attitude values and perceived behavioral control significantly influence students’ smoking cessation behavior. It highlights the need for government regulation, increased tobacco excise, and family support, with recommendations for further research on broader smoking cessation models. Limitations: The study’s subjects were limited to students who quit smoking at seven universities in Soloraya. Future research should include students across Central Java or nationwide and enhance the model by adding moderating variable tests for broader applicability and deeper analysis. Contribution: This study reinforces the Theory of Planned Behavior by introducing pictorial health warnings as an intervening variable and urges the Indonesian Ministry of Health to expand warning displays to enhance fear and awareness of smoking’s negative health impacts.